The Dislocation of the Empty Signifier Freedom as a Tool in Global Political Struggles: A Case Study on RT’s Mini-Series How to Watch the News - Carpentier, Nico (Javnost-The Public, 2022)
Freedom is approached in this article as an empty signifier and as an object of discursive struggle, from a discourse-theoretical perspective. The hegemonic centrality of freedom in Western discourse and identity construction is acknowledged, but at the same time the article argues that hegemony is never total and all-encompassing. In other words, hegemonic constructions are seen as always particular, with their universal claims displaying cracks and gaps. Especially when different discursive communities (e.g. the West and Russia) engage in global discursive struggles, these cracks become visible through dislocatory strategies. The second part of the article then addresses a case study about how this discursive struggle is organised in practice, focussing on the RT mini-series How to Watch the News, which prominently features Slavoj Žižek. The discourse-theoretical analysis demonstrates how the mini-series deconstructs the Western articulation of freedom, in three ways, namely by showing the failures of Western liberal democracies, and the divided nature of Western societies, and by critiquing the individualistic articulation of freedom. The article concludes by pointing to the ambiguities related to the centrality of freedom, the role of RT and the role of Žižek as public intellectual.